Modulatory Effects of Fucoidan on Paracetamol-induced Hepatic Damage and Histological Alterations in Rasbora lateristriata - Sofyantoro, Fajar; Dafa, Maula Haqul; Primahesa, Alfian; Oktaviana, Shintia; Mayani, Olvita; Simanungkalit, Eben Ezer; Prissandi, Anthera Al Firdaus; Nuriliani, Ardaning; Retnoaji, Bambang; Saragih, Hendry T. S. S. G.; Rohmah, Zuliyati; Widiyanto, Slamet; Wijayanti, Nastiti; Septriani, Nur Indah (Biota, 2026)
Paracetamol overdose is a well-documented cause of hepatic injury across vertebrate species, including teleost fish. This study aimed to evaluate the hepatoprotective potential of fucoidan, a sulfated polysaccharide derived from brown algae, against paracetamol-induced liver damage in Rasbora lateristriata. Fish were divided into five experimental groups and exposed to paracetamol (3 mg/L), either alone or in combination with fucoidan at concentrations of 50, 100, or 300 µg/mL, for seven days. Histopathological evaluation of liver tissues was performed using hematoxylin–eosin staining, with semi-quantitative scoring focused on hydropic degeneration, nuclear pyknosis, and necrosis. The results demonstrated that paracetamol exposure induced moderate hepatocellular injury, characterized by cytoplasmic vacuolization, apoptotic nuclear alterations, and necrotic lesions. Co-treatment with fucoidan at 300 µg/mL was associated with reduced severity across all histopathological parameters, indicating partial hepatoprotective effects. In contrast, the 50 µg/mL fucoidan group exhibited paradoxically severe hydropic degeneration despite the absence of pyknosis and necrosis, suggesting a delayed or altered injury profile. Intermediate outcomes were observed at 100 µg/mL. Overall, fucoidan exhibited dose-dependent but inconsistent hepatoprotective effects. The observed histological variability across concentrations suggests that protection may be influenced by factors such as bioavailability, cellular uptake, or interactions with intracellular stress pathways. These findings highlight the need for further mechanistic investigations before fucoidan can be considered a reliable hepatoprotective agent in aquatic toxicology.